Bodies and Persons: Theological Reflections on Transhumanism. Issue 1 (March 2015) - Mercer, Calvin
Abstract: While cautioned by Ted Peters' critique of the more radical brand of transhumanism, in this article the author affirms a greater openness on the part of Christian theology toward the transhumanist/posthumanist program. A key concern will be the place of the human body. Christians affirm an eschatological resurrection of the body. This stands in contrast to radical transhumanists who seek cybernetic immortality—that is, disembodied intelligence. Yet, such intelligence could manifest in a virtual or robotic body. Therefore, it turns out that a posthuman entity, whether an upload or superintelligence, can have a body, albeit qualitatively different from the familiar flesh and blood body. If a pothuman entity can also have personhood, then why could not the promise of God apply?